Clinico-epidemiological profile and socio-demographic characteristics of COVID-19 patients admitted in a tertiary care teaching hospital in Tamil Nadu: a descriptive longitudinal study - Palanichamy, Thiyagarajan (International Journal of Research in Medical Sciences, 2022)
Background: The World Health Organization (WHO), on 11th March 2020 declared severe acute respiratory syndrome by SARS-CoV-2 virus as pandemic disease and renamed it as COVID-19. The case fatality rate ranges from 1.4 to 2%. Amidst several measures to contain the spread and mortalities it is been increasing from the date of its declaration as Public Health Emergency of Global Importance (PHEGI). Our study was aimed to describe the clinical, epidemiological features and socio-demographic characteristics and their associations among the COVID-19 patients admitted in our corona care centres. Methods: A descriptive longitudinal study was done on the laboratory confirmed COVID-19 patients treated in our tertiary care hospital’s corona care centres. Socio-demographic characteristics, co-morbidities, exposure history, PPE use were asked. Symptoms, signs, lab findings, treatments and outcomes were followed-up until discharge or death. The frequencies and statistical associations of variables were analysed using computer software. Results: Out of 145 majority were 21-40 years of age (49.7%) with mean of 40±15.3 years. Majority urban dwellers (76.6%). Smokers and Alcoholics were few (6.9% and 12.4%). 21.4% had health insurance. Mean IP was -7±3.6days. Travel history within 14 days of IP 4.1%. Fever was dominant (82.6%). Prevalence of co-morbidities 50%. Mean duration of hospital stay was 9±3 days. Average gap between diagnosis to negative RT-PCR was 12days. Majority had category 2 treatments (65.5%). Three inpatients died (2.1%). Sex, symptom to RT-PCR test gap, Altered WBC and coagulation profile were showing statistical association with severity. Conclusions: COVID-19 pandemic currently shows low case fatality rate. Clear transmission dynamics and host factors needed for better prevention and control.